2012
DOI: 10.1145/2366145.2366170
|View full text |Cite
|
Sign up to set email alerts
|

Speculative parallel asynchronous contact mechanics

Abstract: We extend the Asynchronous Contact Mechanics algorithm [Harmon et al. 2009] and improve its performance by two orders of magnitude, using only optimizations that do not compromise ACM's three guarantees of safety, progress, and correctness. The key to this speedup is replacing ACM's timid, forward-looking mechanism for detecting collisions-locating and rescheduling separating plane kinetic data structures-with an optimistic speculative method inspired by Mirtich's rigid body Time Warp algorithm [2000]. Time wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Due to limitations of our collision handling implementation we were not able to reproduce their densest experiment with φ = 22%. Doing so would require more robust collision handling, such as described by Ainsley et al [2012], that could accommodate large stacks of arbitrarily close surfaces.…”
Section: Crumpling Comparisonmentioning
confidence: 99%
“…Due to limitations of our collision handling implementation we were not able to reproduce their densest experiment with φ = 22%. Doing so would require more robust collision handling, such as described by Ainsley et al [2012], that could accommodate large stacks of arbitrarily close surfaces.…”
Section: Crumpling Comparisonmentioning
confidence: 99%
“…ARCSim adapts the elastic model formulation from several different approaches [Bridson et al 2003;Grinspun et al 2003;Müller and Gross 2004;Wang et al 2011] and used different algorithms for collision handling. There has been a rich body of research on contact and collision for cloth simulation [Bridson et al 2002;Baraff et al 2003;Harmon et al 2008;Kaufman et al 2008;Otaduy et al 2009;Harmon et al 2009;Tang et al 2010;Miguel and Otaduy 2011;Ainsley et al 2012]. The core algorithm for collision handling in ARCSim is based on Bridson et al [Bridson et al 2002], who uses a geometry-based repulsive impulse to handle collision robustly.…”
Section: Related Workmentioning
confidence: 99%
“…Applications considered in this paper include (i) asynchronous variational integrators (AVI), which are used in computational mechanics and in graphics for solving complicated contact mechanics problems [27] like simulating the tying of ribbons and the crushing of rabbits in a trash compactor [1,18], (ii) discrete-event simulation (DES) [9], (iii) the simulation of collisions between a set of moving bodies like billiard balls [2,18], and (iv) graph analytics algorithms such as Breadth-First Search (BFS), Minimumweight Spanning Tree (MST), and tree traversals. The inadequacy of conventional task graphs for these applications arises from the fact that the dependence graph computed from a particular program state may not remain valid after a task has executed because new tasks may have been created and dependences between existing tasks may have changed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, sequential DES implementations process events in increasing time order by maintaining a priority queue of events sorted by their time-stamp; it can be shown that it is correct to process the earliest event, which is a safe source in the DAG. These kinds of algorithms are called ordered algorithms in the TAO classification of algorithms [34] because the execution of the program must respect the priority order between tasks (in contrast, tasks in unordered algorithms can be executed in any order without violating program semantics) 1 . Some of these applications have been parallelized previously by other researchers using problem-specific techniques: for example, AVI has been parallelized by Huang et al [19] using "edge-flipping" DAGs, described in Sections 2.1 and 4.1, but this technique cannot be used for any of the other problems considered in this paper.…”
mentioning
confidence: 99%
See 1 more Smart Citation